Islamization and Growth of Islamic Educational Institutions - Vegia Oviensy; Duski Samad; Firdaus Sutan Mamad; Rosen, Christopher; Sabrina Adia binti Mohd Shahrizal (Yayasan Cendekia Gagayunan Indonesia, 2025)
This research discusses the process of Islamization and its impact on the development of Islamic educational institutions in historical and contemporary perspectives. Islamization is understood as a systematic effort to integrate Islamic values, principles, and epistemology into various aspects of life, including in the realm of education. This research aims to examine the dynamics of the development of Islamic educational institutions such as madrasas, Islamic boarding schools, and Islamic universities in responding to social, political, and global challenges. The method used is a qualitative approach with literature review techniques on relevant literature. The results of the study show that the process of Islamization of education is not only influenced by religious encouragement, but also by the need for integration between Islamic sciences and modern sciences. These findings confirm that Islamization has become an important factor in strengthening Islamic identity and encouraging innovation in the curriculum and learning system in Islamic educational institutions. This study is expected to make a conceptual contribution to the development of Islamic education that is adaptive to the dynamics of the times.